PREDIKSI NILAI INDEKS EKSPOR SUSU SEGAR DI INDONESIA MENGGUNAKAN ALGORITMA BACKPROPAGATION - Holil Asy’ari; Zaehol Fatah (Jurnal Riset Sistem Informasi, 2025)
The results of research on the value of exports in Indonesia can be concluded that the architectural model can make predictions with 100% accuracy with a short training time. In addition, by looking at the results of testing on architecture, it can be seen that both the speed and the prediction results, it can be concluded that the value of exports in Indonesia is increasingly declining. For future research, research should use a different algorithm or the Backpropagation algorithm can be optimized with other algorithms, such as conjugate gradient and so on, that is, the research was first carried out using the backpropagation algorithm, then after knowing the results, calculations were carried out with the algorithm. other. After that, a comparison is made between the results of backpropagation with the results of other algorithms. Images or graphs of each algorithm used, or a graphic image of the comparison of the previous data with the data that has been generated using the algorithm.